2022
DOI: 10.1002/adfm.202202207
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Gas Sensor Detecting Hydroxyl Groups with Phase Transition Based on Eco‐Friendly Lead‐Free Metal Halides

Abstract: An electrical and optical responsive chemical-semiconductor gas sensor is developed using Cu(I) halides with a phase transition mechanism. Cu(I) materials exhibit reversible phase transitions between the Cs 3 Cu 2 I 5 and CsCu 2 I 3 with different properties, owing to the formation/destruction of the Cs-I and Cu-Cu bonding when the hydroxyl groups are attached/detached. Among various toxic and atmospheric gases, a Cu(I)-based gas sensor has high selectivity in detecting the hydroxyl group, and the highest sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Moreover, switching between multiple types of inorganic units leads to changing optical properties that offer new application prospects for copper halides. 29–34 This reversible transformation between two hybrid copper halides under external stimuli was recently reported, demonstrating the potential of solvent-induced phase transition behavior in anti-counterfeiting. 35–37 During this submission, Lei published a reversible single-crystal to single-crystal transition between (ETPP) 2 Cu 4 Br 6 and (ETPP)CuBr 2 very recently.…”
Section: Introductionsupporting
confidence: 60%
“…Moreover, switching between multiple types of inorganic units leads to changing optical properties that offer new application prospects for copper halides. 29–34 This reversible transformation between two hybrid copper halides under external stimuli was recently reported, demonstrating the potential of solvent-induced phase transition behavior in anti-counterfeiting. 35–37 During this submission, Lei published a reversible single-crystal to single-crystal transition between (ETPP) 2 Cu 4 Br 6 and (ETPP)CuBr 2 very recently.…”
Section: Introductionsupporting
confidence: 60%
“…Cs–Cu–I perovskite, as a type of lead-free perovskite, has shown excellent properties in the field of photoelectric devices due to being environmentally friendly, its high photoluminescence quantum yield, and its excellent air stability. , Although 1D CsCu 2 I 3 and 0D Cs 3 Cu 2 I 5 have different crystal structures, they exhibited certain gas-sensitive sensing properties, in addition to ultraviolet light detection properties. For instance, Choi et al proposed a novel semiconductor and gasochromic multimodal responsive gas sensor based on the gas-induced phase transition mechanism of Cs 3 Cu 2 I 5 . Sun et al reported nanostructured-network gas sensors based on lead-free CsCu 2 I 3 , which exhibited excellent room-temperature NO 2 sensing properties, including an ultralow limit of detection, excellent repeatability, and good selectivity .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Choi et al proposed a novel semiconductor and gasochromic multimodal responsive gas sensor based on the gas-induced phase transition mechanism of Cs 3 Cu 2 I 5 . 33 Sun et al reported nanostructured-network gas sensors based on lead-free CsCu 2 I 3 , which exhibited excellent room-temperature NO 2 sensing properties, including an ultralow limit of detection, excellent repeatability, and good selectivity. 34 However, the detection performance of Cs–Cu–I perovskite materials for other gases has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, metal halide perovskite-based gas sensors have become the frontier hotspot in room-temperature-operating gas sensors due to their tunable bandgap, high defect tolerance, low defect density, high carrier concentration, and high carrier mobility . Currently, RT gas sensors based on metal halide perovskites have made great progress. Nuraini et al have successfully applied a methylammonium lead iodide (MAPbI 3 ) perovskite thin film to an RT volatile organic compound (VOC) gas sensor, including ethanol, methanol, and so on . Chen et al synthesized an RT sensor based on the porous network of CsPbBr 3 , which can detect 1 ppm ethanol and acetone with a sensitivity ( I VOC / I air – 1) of ∼0.03 .…”
mentioning
confidence: 99%